ACADEMIC AND ADAPTATION DIFFICULTIES OF MEDICAL STUDENTS WITH LOW ACADEMIC ACHIEVEMENT IN THE FIRST TWO YEARS - Fairus, Fadhila Nuralifa; Titaley, Christiana R.; Manuputty, Amanda Gracia; Malakauseya, Maxwell Landri Vers; Taihuttu, Yuniasih M. J.; Bension, Johan B. (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Academic difficulties and lack of adaptation ability of students to their educational environment are often encountered in the early period of their education, including for those enrolled in medical faculties. The academic difficulties encountered could be reflected in the low academic achievement of students. This study aimed to explore the academic difficulties and adaptation processes of students with low academic achievement (GPA <2.50) in the first two years at the Faculty of Medicine, University of Pattimura (UNPATTI), Ambon.Methods: This study used a qualitative method involving 23 informants from the first and second year at the Faculty of Medicine UNPATTI who had low academic achievement (GPA <2.50). Data were collected from March to April 2022 using Focus Group Discussion (FGD) and in-depth interviews (IDI) techniques. Data analysis was performed using the thematic analysis method based on the research objectives.Results: This study shows that the academic difficulties of first-two-year students with low academic achievement are influenced by several factors, including the transition from school to university, tight scheduling, difficulty in understanding lecture material, and the online lecture system due to the COVID-19 pandemic occurred since 2020. These difficulties were also exacerbated by student attitudes, family influence, and the socio-economic environment.Conclusion: It is necessary to identify students who experience academic difficulties as early as possible. This will help educational institutions assist them, including by strengthening the role of academic supervisors and peer mentors for students in need.